Pengaruh Kualitas Pelayanan dan Persepsi Harga Terhadap Kepuasan dan Niat Berkunjung Kembali Pada The Sila’s Agrotourism - Putu Laksmita Dewi Rahmayanti; I Wayan Suartina; Nyoman Surya Wijaya; Miko Andi Wardana; Komang Sumerta; Ni Nyoman Kerti Yasa (Papanda Publisher, 2022)
Covid-19 has had a major impact on the tourism sector. It is difficult for foreign tourists to enter Bali due to strict government regulations in an effort to prevent the spread of Covid-19. Therefore, Bali is currently very dependent on the visit of domestic tourists. The SILA'S Agrotourism is one of the tourist destinations in Bali that has been around for a long time, and has a potential tourist attraction and is able to attract tourist visits, especially domestic tourists. However, currently it is not optimally able to attract tourist visits, because many new tourist attractions have begun to emerge. This study aims to explain the effect of service quality on satisfaction and intention to revisit at The SILA'S Agrotourism. The type of research used is associative research, with sampling using non-probability techniques with purposive sampling method, on respondents who are tourist visitors to The SILA'S Agrotourism. Quantitative data analysis technique uses Structural Equation Model Partial Least Square (SEM-PLS) analysis with SmartPLS 3.0 software. The results of this study provide several conclusions that the overall hypothesis formulation has a significant effect, service quality has a positive and significant effect on satisfaction, service quality has a positive and significant effect on revisit intentions, and satisfaction has a positive and significant effect on revisit intentions.